Ekplorasi Konsep Dinamika Rotasi pada Tari Banjarkemuning Asal Sidoarjo sebagai Sumber Pembelajaran Fisika Berbasis Etnofisika - Achmad Maulana Satria Putra; Rif'ati Dina Handayani; Trapsilo Prihandono (Pendidikan Fisika Universitas Nurul Huda, 2024)
Physics as a part of natural science can not be separated with indigenous knowledge. This research aims to explore the physics concepts of dynamics rotation in Tari Banjarkemuning, Sidoarjo, East Java. This qualitative research using a content analysis steps which divided into unitizing, sampling, coding, reducing, inferring, and narrating. Data were collected by observation, interviews, and literature study. The dynamics rotation shows at variety motion of embat-embat, silatan, and ceklekan. The rotational hand's movement in embat-embat identic with concept of torque. The dancer's hands has folded while make a rotational movement at silatan identic with concept of moment inertia. The dancers shakes the sampur and fold both arms toward her chest as it spin which related with a law conservation of angular momentum. Thus, the research can used as a reference in innovation of contextual physics learning with ethnophysics teaching materials approach